2019
DOI: 10.1111/jzo.12647
|View full text |Cite
|
Sign up to set email alerts
|

Feline predator–prey relationships in a semi‐arid biome in Brazil

Abstract: The spatiotemporal distribution of a predator within an environment tends to be synchronized with that of its prey, to maximize the efficiency of its hunting behavior. However, small predators may also be obliged to avoid potentially agonistic encounters with larger predators due to interspecific competition and intraguild predation. We used occupancy models and indices of temporal overlap to evaluate whether the occurrence of prey species, ocelots (Leopardus pardalis) and top predators (puma Puma concolor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 44 publications
(75 reference statements)
0
17
0
Order By: Relevance
“…Our study concluded that the nocturnal paca should be an important prey species for the nocturnal ocelot ( Table 2 ). Other studies have found a marked temporal overlap between ocelot and paca, with paca in Colombia being mainly nocturnal and paca in Brazil being strictly nocturnal during the rainy season and predominately nocturnal during the dry season ( Dias et al 2019 ; García-R et al 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…Our study concluded that the nocturnal paca should be an important prey species for the nocturnal ocelot ( Table 2 ). Other studies have found a marked temporal overlap between ocelot and paca, with paca in Colombia being mainly nocturnal and paca in Brazil being strictly nocturnal during the rainy season and predominately nocturnal during the dry season ( Dias et al 2019 ; García-R et al 2019 ).…”
Section: Discussionmentioning
confidence: 92%
“…We calculated the Δ 4 estimator when even the smallest sample of each pairwise comparison was >75 photographs; we used the Δ 1 estimator when the number of photographs was <75 for at least one species of the pair (Linkie & Ridout, ; Meredith & Ridout, ). Then, we estimated the 95% confidence intervals (hereafter, 95% CI) of the coefficient estimator, based on 10 000 bootstrap replicates (Dias et al , ). We only considered species with at least 20 records.…”
Section: Methodsmentioning
confidence: 99%
“…We categorized the activity of each target species as being predominantly nocturnal when most of the activity occurred between 1 h after the sunset and 1 h before the sunrise. For strictly nocturnal species, we considered the ones whose activity periods were exclusively recorded during the night (Dias et al, 2018(Dias et al, , 2019a. We defined the cathemeral period occurring between 1 h before and after sunrise and sunset (see Massara et al, 2018).…”
Section: Discussionmentioning
confidence: 99%